HUBUNGAN NAIK TURUN TANGGA DENGAN KEMEMPUAN BLOCK BOLA VOLI TERHADAP SISWA KELAS X MA DAAR ET-TAQWA PETIR KABUPATEN SERANG - Nana Hadi Permana; Ridwan Sudirman (Jurnal Pendidikan Dasar Setiabudhi, 2021)
This research method is a quantitative method with a correlation approach. This sampling technique is called random sampling of the entire class. This technique is intended to make researchers more efficient because they do not require many objects. In this process, the researcher gives equal rights to each subject to get the opportunity to be a sample. Thus the sample of this study amounted to 30 students as respondents. The conclusions in this study are: The results of statistical analysis between there is a significant relationship between the method of going up and down stairs (X) and the ability to block volleyball, the value of t = 2.39, t table = 0.654 means that there is tolerance between the two variables. With the correlation table r = 0.45 is in the strong category. Thus, the alternative hypothesis of a significant relationship between the method of going up and down stairs (X) and the ability to block volleyball, then 2.39 > 0.654 the hypothesis Ha is accepted. It can be concluded that the hypothesis Ha stated: "there is a significant relationship between the method of going up and down stairs and the volleyball block ability of class X Daar Et-Taqwa Petir students, Serang Regency. This is because it is proven true. On the other hand, the null hypothesis (Ho) is rejected because it is not proven true. Keywords: Up and Down stairs and Block Ball Abstrak Metode penelitian ini metode kuantitatif dengan pendekatan korelasi. Teknik sampling ini disebut random sampling dari keseluruhan kelas. Teknik ini dimaksudkan agar peneliti lebih efisien karena tidak membutuhkan banyak objek. Pada proses ini pula peneliti memberikan hak yang sama kepada setiap subjek memperoleh kesempatan menjadi sampel. Dengan demikian sampel penelitian ini berjumlah 30 siswa sebagai responden. Kesimpulan dalam penelitian ini adalah: Hasil analisis statistik antara ada hubungan yang signifikan anatara metode naik turun tangga (X) dan kemampuan Block bola voli diperoleh nilai t= 2,39, ttabel = 0,654 ini berarti terdaat tolerasi diantara kedua variabel tersebut. Dengan tabel kolerasi r = 0,45 berada pada kategori kuat. Dengan demikian, hipotesis alternatif hubungan yang signifikan antara metode naik turun tangga (X) dan kemampuan block bola voli, maka 2.39 > 0.654 hipotesis Ha diterima. Dapat disimpulkan bahwa hipoteis Ha yang dinyatakan : “adanya hubungan yang sigifikan antara metode naik turun tangga dan kemampuan blok voli siswa kelas X Daar Et-Taqwa Petir Kabupaten Serang. Hal ini karena terbukti kebenarannya. Sebaliknya hipotesis nihil (Ho) ditolak karena tidak terbukti kebenarannya. Kata kunci : Naik Turun Tangga dan Block Bola